Pre/texts for an Emerging Dramaturgy: Reconceiving Models of Authorship in Text-based Performance - Romanello, Filippo (Mimesis Journal, 2017)
If in pure immanence all meaning should emerge freely within a system (e.g. is a fully spontaneous performance, or in certain ways of life), and in pure transcendence all meaning be organised from without (e.g. by an author, or a god), this project explores how a theatre- making methodology based on a pre-existing, single-authored text, can still achieve high degrees of immanence in performance. By investigating new approaches to writing and dramaturgy - approaches that facilitate the actor’s spontaneous reactions to the text - the project aims to demonstrate that repetition can generate different e effects should it not claim to reproduce an original one. In other words, the performance of repetition of a structure such as text, attempting to detach itself from what its originating text may claim to signify, can find a significance of its own. Therefore, if a theatre of representation betrays itself by attempting to remain faithful to its originating idea, a theatre of immanence needs to betray that idea in order to be faithful to itself. The creative practice element of the research is twofold: the development of textual material with certain characteristics useful for improvisation, and the testing of that material with performers in the studio. Dramaturgy in this context is the facilitation of this embodied process of scenic composition. This article will outline the former aspect of the practice and discuss a sample extract from a work in progress.